Investigating the utility of incorporating stable isotope analysis into ecosystem models: an oyster aquaculture case study - Noah Motz; Brendan Campbell; Rileigh E. Hudock; Tess Avery; Benjamin Marsaly; Howard Townsend; James Vasslides; Edward Hale; Aaron Carlisle (Ecological Modelling, 2026)

Genetic ancestry proportion influences risk of adverse events from tuberculosis treatment in Brazil - Jacqueline A. Piekos; Gustavo Amorim; Felipe Ridolfi; Marcelo Cordeiro-Santos; Afrânio L. Kritski; Marina C. Figueiredo; Bruno B. Andrade; Adalberto R. Santos; David W. Haas; Timothy R. Sterling; Valeria C. Rolla; Digna R. Velez Edwards; et al. (Human Genetics, 2026)
Tuberculosis (TB) treatment is highly effective, but response to therapy varies by geography and population subgroups. We assessed differences in TB treatment response in a representative and heterogeneous Brazilian population. We estimated genetic ancestry according to major genetic ancestry groups (African, European, and Amerindian) in the Regional Prospective Observational Research in Tuberculosis (RePORT)-Brazil cohort using ADMIXTURE software. RePORT-Brazil is an observational prospective cohort study of individuals with newly-diagnosed, culture-confirmed, pulmonary TB. Outcomes attributed to TB treatment included Grade 2 or higher adverse drug reaction (ADR), Grade 3 or higher ADR, hepatic ADR, and failure/recurrence. Genetic ancestry proportions were evaluated as predictors in univariate and multivariable logistic regression models for each outcome, and in stratified models for each genetic ancestry group. There were 930 pulmonary TB patients included in this study. In multivariable models we observed a decreased risk of Grade 2 + ADR when African ancestry proportion increased by 10% (Odds Ratio [OR] 0.41, 95% Confidence Interval [CI] 0.20–0.85) and an increased risk for Grade 2 + ADR with increasing European genetic ancestry (OR 2.33, 95% CI 1.14–4.76). In secondary analyses evaluating the interaction of HIV and genetic ancestry, we observed a statistically significant interaction between HIV and African genetic ancestry, but significantly decreased risk for Grade 2 + ADR with increasing African ancestry proportion. There were no associations with Amerindian genetic ancestry or for other treatment outcomes. In this Brazilian TB cohort, increased toxicity risk was associated with decreased African and increased European ancestry proportion.

Miocene flood basalts in NW Spitsbergen: Emplacement environment and Arctic paleoclimate context - Maria Telmon; Sten- Andreas Grundvåg; Kim Senger; Sverre Planke; Rafael Kenji Horota; Peter Betlem; Dmitrii Zastrozhnov; Alexander Minakov; Benjamin Edwards; Kasia K. Sliwinska; Matthew J. Pound; Andrea Di Capua (Journal of Volcanology and Geothermal Research, 2026)

Termites in rural Nigeria: exploring agricultural damage and management strategies in smallholder farming systems - Manuela Carnaghi; Stephanie Mdzuami Avar-Tsue; Davide Bosio; Stephen Young; Benjamin Ahule; Hans Dobson; Edward Omudu (Crop Protection, 2026)

Reconstructing prehistoric land cover and landuse in complex ‘blue-green’ landscapes - Kimberley L. Davies; M. Jane Bunting; Willem Koster; Nicki J. Whitehouse; Michelle Farrell; Henry Chapman; Jason R. Kirby; J. Edward Schofield; Phil Barratt; Benjamin Gearey; Nika Shilobod (Vegetation History and Archaeobotany, 2026)

Decade-scale recovery of the Eyjafjallajökull ice cap, Iceland, after the 2010 summit eruption - Linda Sobolewski; Magnús Tumi Gudmundsson; Eyjólfur Magnússon; Joaquín M. C. Belart; Thomas R. Walter; Benjamin R. Edwards; Karuna Mira Sah; William Kochtitzky (Bulletin of Volcanology, 2026)
Several eruptions at glaciated volcanoes have been witnessed during the last two centuries. However, most studies have focused on understanding the volcanic products or the hazard implications. Less attention has been put into analyzing the long-term effects on the glaciers. The 2010 summit eruption of Eyjafjallajökull (Iceland) provides an excellent opportunity to study such impacts by investigating how individual areas of the ice cap have changed with time. These include (i) the summit caldera (formation of vents/lava), (ii) the southern flank (short-lived eruption fissure), and (iii) the outlet glacier Gígjökull (lava propagation). We used high-resolution satellite data acquired by Pléiades and SPOT5, complemented by airborne LiDAR, to calculate elevation and volume changes of the glacier over varying time periods between 2008 and 2024. From August 2010 to August 2014, the main vent showed an elevation increase of ~ 80 m; visible eruption impacts on the southern flank have completely vanished; Gígjökull significantly recovered. However, the ice cap overall is shrinking. The area decreased from 72.3 km 2 (2010) to 63.5 km 2 (2024), with an average elevation change of −8.3 m. The caldera and Gígjökull did not follow this trend and showed an average elevation increase of ca. 13.4 m (1.0 m/year). We hypothesize that the depressions formed by the eruption acted as traps for drifting snow in winter, resulting in a local thickening rate far exceeding the average winter accumulation. Although the recovery is exceptional, the volume still only corresponds to around 50% of the ice loss caused by the eruption.

Aquaculture-aided aquatic restoration and conservation: Highlights, challenges, and key lessons from global case studies - Emilee D. Benjamin; Casey A. Murray; Ricardo Riquelme; Edward Camp; Andrew Jeffs; Joshua Patterson; Aaron Pilnick; Jennifer Gumm; Taylor Lipscomb; Gesica Aroca; Marcela Ávila; Holly Richards; et al. (Fisheries Research, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

A Jelly-Eating Hitchhiker in the Mediterranean: Molecular Identification of Brachyscelus rapacoides Stephensen 1925 (Amphipoda: Brachyscelidae) in Greece - Konstantinos Kalaentzis; Paraskevi Louizidou; Gerasimos Kondylatos; Elisavet Kaitetzidou; Lyndall Pereira da Conceicoa; Mara Lawniczak; Alex Makunin; Jack Monaghan; Paul Heath; Craig Corton; James Watts; Michelle Smith; et al. (Thalassas: An International Journal of Marine Sciences, 2026)
The hyperiid amphipod Brachyscelus rapacoides is a warm-water species associated with gelatinous zooplankton. In the Mediterranean it has been reported in association with Rhopilema nomadica in both Israel and Turkey. Here, we document the first record of B. rapacoides in Greek waters, representing the first confirmed record for Europe, based on both morphological examination and DNA barcoding of the mitochondrial COI gene. Specimens were collected from the umbrella of infested R. nomadica from two localities in the southeastern Aegean Sea. Diagnostic morphological characters, particularly the dentition of gnathopods 1–2 and male antennal morphology, agree with published redescriptions of the species. Phylogenetic analyses placed the studied specimens within B. rapacoides , clearly separated from congeners. This finding extends the known distribution of the species westwards in the Mediterranean and further supports its close ecological association with R. nomadica . The record highlights the role of gelatinous hosts in facilitating dispersal of symbiotic hyperiids and underscores the importance of integrating molecular tools and citizen science observations for early detection of overlooked pelagic associates.

Observation of Rockfall in the Thermal Infrared - Edward C. Wellman; Kirk W. Schafer; Chad P. Williams; Greatness H. Ojum; Julia J. Potter; Leonard D. Brown; Benjamin Meyer; Bradley J. Ross; John Kemeny (Rock Mechanics and Rock Engineering, 2026)

Evaluation of siRNA-mediated knockdown of heat shock protein 16.2 in adult Acropora cervicornis - Edward P. Gniffke; Benjamin D. Young; Keir J. Macartney; Michael S. Studivan; Ian C. Enochs; Erin E. Easton (Frontiers in Marine Science, 2026)
Acropora cervicornis is a critically endangered Caribbean coral species facing a precipitous decline due to disease and thermal bleaching. To combat the loss of ecologically important reef-building corals, novel molecular approaches can be used to understand mechanisms of resilience and ultimately provide a means to modulate coral performance. In this study, we tested a recently developed method for gene knockdown in adult corals that utilizes short interfering RNAs (siRNAs) and the RNA interference pathway. The Heat Shock Protein 16.2 (HSP16.2) gene in fragments of adult A. cervicornis was targeted for knockdown using a single siRNA construct. RT-qPCR analysis of HSP16.2 gene expression was performed between filtered seawater, no template control siRNA (NTC), and siRNA targeting HSP16.2 across four genotypes of A. cervicornis with known differences in thermal susceptibility (two heat-tolerant and two heat-susceptible genotypes). There was no significant difference in HSP16.2 gene expression due to the treatment of HSP16.2 siRNAs versus controls, but we did identify a single genotype-driven effect that corroborates evidence that A. cervicornis heat tolerance is driven largely by genotype. No difference in photophysiological performance or mortality was observed between experimental and control treatments. There were, however, some differences in mortality and HSP16.2 expression among genotypes. Our results reveal that siRNA-mediated knockdown was not successful for this species and gene and thus further optimization is needed prior to broader applicability of siRNA-mediated knockdown in corals. We provide an assessment of potential methodological improvements to support the development of future reverse-genetics studies in corals.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

A laboratory-based spectrometer intercomparison for the measurement of snow spectra - Benjamin M. Roberts-Pierel; Christopher J. Crawford; Steven W. Brown; Raymond F. Kokaly; Kelly E. Gleason; Anne W. Nolin; Edward H. Bair; Brenton A. Wilder; Anton J. Surunis; S. McKenzie K. Skiles; Joachim Meyer; Allyson E. Fitts; et al. (Cold Regions Science and Technology, 2026)

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

From magma to macrophage: the grand challenges of volcanic environments - Catherine A. Mériaux; Edward Ntim Gasu; Guillaume Nyagatare; Vicky Ruganzu; Philbert Ntivuguruzwa; Mwumvaneza Mutagoma; Atalay Ayele; Julyan H. E. Cartwright; Valérie Cayol; Laurent Charlet; Claudia Corradino; Antonio Costa; et al. (Bulletin of Volcanology, 2026)
The interdisciplinary study of volcanic processes, which extend across all timescales and lengths, requires a multitude of approaches, ranging from analogue and numerical modelling to observations and fieldwork and extending to mathematics. A conference was held at the East African Institute for Fundamental Research, affiliated with the University of Rwanda, a country which, along with the Democratic Republic of Congo, presents a unique geodynamic context. Located along the East African Rift, an active seismic region, Rwanda is close to two of Africa's most active volcanoes, including Nyiragongo, which overlooks Lake Kivu, a deep volcanic lake rich in dissolved carbon dioxide and methane, the latter of which is used for electricity generation. In this context, the conference addressed many “classic” volcanological topics and their modern advances, such as multiphase lava flows, subsurface magma propagation, seismic and deformation signals from a volcano, modelling of volcanic emission dispersion, and volcanic lakes. Yet, it broadened the discussion to the volcanic particle-water interface and its impact on soils, volcanoes and climate change, and volcanoes and health. This article aims to highlight and share the richness of the integration and interconnectedness of the various questions related to a volcanic environment, as well as their impact on society. Ultimately, this conference also demonstrated the importance of promoting science in Africa and developing countries so that the next generation of African researchers is equipped to address the challenges facing their nations.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Ex vivo Tissue Provides Insight into Bleb Dynamics During Large-Volume Subcutaneous Injection - Taeki Kim; Pierre Artus; Benjamin Berat; Edward Tang; James Bird (Pharmaceutical Research, 2026)

Short-term effects of Greenlandic glacial rock flour on soil physical properties and maize yield - William Akortey; Eric Oppong Danso; Christiana Dietzen; William Amponsah; Emmanuel Arthur; Bernard Kwabena Boadi Mensah; Peter Bilson Obour; John Bright Amoah Nyasapoh; Daniel Amoako Darko; Selorm Yaotse Dorvlo; Edward Benjamin Sabi; Stephen Abenney-Mickson; et al. (Nutrient Cycling in Agroecosystems, 2026)
Greenlandic glacial rock flour (GRF) serves as a valuable source of silicate minerals for CO₂ uptake through enhanced weathering. Additionally, its physico-chemical properties may influence soil hydro-physical characteristics and may also have a separate effect on crop yields. This study evaluated the effects of GRF application at 50 and 100 t/ha, along with an unamended control, on soil water content at field capacity (FC), plant-available water (PAW), saturated hydraulic conductivity (K sat ), and dry aggregate stability (DAS) over 120 days. Separately, maize dry matter yield (DMY) was assessed after 40 days of growth. The experiment was conducted across four soil textures, comprising coarse-textured soils (sand and sandy loam) and fine-textured soils (sandy clay loam and clay). The 100 t/ha application had the most significant ( p < 0.05) impact on soil properties and maize yield, while the 50 t/ha rate showed intermediate but inconsistent effects. In fine-textured soils, the 100 t/ha treatment increased FC by 15% and PAW by 27% compared to the control, whereas in coarse-textured soils, FC and PAW rose by 29% and 26%, respectively. However, Ksat decreased by 47% in fine-textured soils and 34% in coarse-textured soils compared to the control. Maize DMY for the 100 t/ha rate increased by 18% in coarse-textured soils and 38% in fine-textured soils relative to the control. These findings suggest that GRF amendment improved hydro-physical properties more in coarse-textured soils but increased yield more in fine-textured soils, and may serve as a useful co-benefit of enhanced rock weathering.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Implications of depensation on oyster recruitment, population collapse, restoration, and sustainable fisheries management - Edward V. Camp; William Pine; William R. Casola; Emilee D. Benjamin; Chad Palmer; Kotryna Klizentyte; Kai Lorenzen (Fisheries Research, 2026)

Late Quaternary environmental change in eastern Beringia - Alistair J. Monteath; Mary E. Edwards; Duane Froese; Lesleigh Anderson; Benjamin V. Gaglioti; Scott L. Cocker; Julie Brigham-Grette; Matthew J. Wooller; Bruce Finney; Mark B. Abbott (Quaternary Science Reviews, 2025)

Can Solar‐Powered Irrigation Systems Naturally Meet Crop Water Requirements? Proof of Concept From a Case Study in Sub‐Saharan Africa - Eric Oppong Danso; Christiana Dietzen; William Akortey; Bernard Kwabena Boadi Mensah; Peter Bilson Obour; John Bright Amoah Nyasapoh; Ebenezer Agyapong; Elorm Grace Ayayi; Nana Oduro Osei Bonsu; Michael Osei Adu; Emmanuel Arthur; Jacob Ulzen; et al. (Irrigation and Drainage, 2025)
Irrigation scheduling is crucial for ensuring precise water delivery to crops. However, in many sub‐Saharan African irrigation schemes, water is applied without considering crop water needs, resulting in low crop water productivity and low yields. Solar‐powered irrigation systems can automatically meet these needs by utilizing solar radiation, which drives both evapotranspiration and solar panel power production for pumping. This study aimed to integrate irrigation scheduling into a solar‐driven irrigation system and assess the impact of meteorological variables on reference evapotranspiration (ET o ) in Ghana. A 50‐watt solar panel powered a 12‐V submersible pump, with a flow meter installed on the outlet pipe for hourly volume of water pumped (VWP) data readings. These data were used to examine correlations between solar radiation (R s ) and ET o , as well as between R s and VWP. Partial correlation analyses were used to assess the relative influences of R s , wind speed (U 2 ), relative humidity (RH) and air temperature (T air ) on ET o across 10 locations in Ghana's agroecological zones. The study revealed a strong linear correlation between the hourly R s and ET o ( R 2 > 0.9) and between the hourly R s and VWP ( R 2 = 0.8). The VWP was sufficient to meet crop‐water demand year‐round. Solar radiation was consistently the primary meteorological factor influencing ET o in Ghana.

Evaluation of multi-channel ceramic tubular membranes for high-salinity water desalination by vacuum membrane distillation - Rebecca Lee; N.M. Srivatsa Bettahalli; Marianne Pemberton; Edward Wazer; Benjamin Anacleto; Johann Schnittger; Marcus Weyd; Ingolf Voigt; Joachim Koschikowski; Manish Kumar; Jeffrey R. McCutcheon (Desalination, 2025)

Intracellular carbon storage of microorganisms and resulting C sequestration in biosolids-amended agricultural soil - Guanglong Tian; Olawale Oladeji; Benjamin Morgan; Essam El-Naggar; Albert Cox; Heng Zhang; Edward Podczerwinski (Soil Biology and Biochemistry, 2025)

A Review of Abrupt Permafrost Thaw: Definitions, Usage, and a Proposed Conceptual Framework - Hailey Webb; Matthias Fuchs; Benjamin W. Abbott; Thomas A. Douglas; Clayton D. Elder; Jessica Gilman Ernakovich; Eugenie S. Euskirchen; Mathias Göckede; Guido Grosse; Gustaf Hugelius; Miriam C. Jones; Charles Koven; et al. (Current Climate Change Reports, 2025)
Purpose of Review We review how ‘abrupt thaw’ has been used in published studies, compare these definitions to abrupt processes in other Earth science disciplines, and provide a definitive framework for how abrupt thaw should be used in the context of permafrost science. Recent Findings We address several aspects of permafrost systems necessary for abrupt thaw to occur and propose a framework for classifying permafrost processes as abrupt thaw in the future. Based on a literature review and our collective expertise, we propose that abrupt thaw refers to thaw processes that lead to a substantial persistent environmental change within a few decades. Abrupt thaw typically occurs in ice-rich permafrost but may be initiated in ice-poor permafrost by external factors such as hydrologic change (i.e., increased streamflow, soil moisture fluctuations, altered groundwater recharge) or wildfire. Summary Permafrost thaw alters greenhouse gas emissions, soil and vegetation properties, and hydrologic flow, threatening infrastructure and the cultures and livelihoods of northern communities. The term ‘abrupt thaw’ has emerged in scientific discourse over the past two decades to differentiate processes that rapidly impact large depths of permafrost, such as thermokarst, from more gradual, top-down thaw processes that impact centimeters of near-surface permafrost over years to decades. However, there has been no formal definition for abrupt thaw and its use in the scientific literature has varied considerably. Our standardized definition of abrupt thaw offers a path forward to better understand drivers and patterns of abrupt thaw and its consequences for global greenhouse gas budgets, impacts to infrastructure and land-use, and Arctic policy- and decision-making.

3D printed microtissue cassettes enabling high throughput proton radiobiological assays - Chih-Tsung Yang; I-Chun Cho; Ching-Fang Yu; Edward Cheah; Tesi Liu; Yi-Ping Lin; Sing-Yu Hu; Jyun-Wei Jheng; Ivan Kempson; Tsi-Chian Chao; Sen-Hao Lee; Eva Bezak; et al. (Analytica Chimica Acta, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

The Volcanoes of the World database - Benjamin J. Andrews; Edward Venzke; Elizabeth Cottrell; Sally S. K. Sennert; Kadie L. Bennis; A. E. J. Crafford (Bulletin of Volcanology, 2025)

Tolerable magnitudes for induced seismicity at offshore carbon capture and storage projects - James P. Verdon; Ryan Schultz; Benjamin Edwards (International Journal of Greenhouse Gas Control, 2025)

The function of love: A signaling-to-alternatives account of the commitment device hypothesis - Benjamin Gelbart; Kathryn V. Walter; Daniel Conroy-Beam; Casey Estorque; David M. Buss; Kelly Asao; Agnieszka Sorokowska; Piotr Sorokowski; Toivo Aavik; Grace Akello; Mohammad Madallh Alhabahba; Charlotte Alm; et al. (Evolution and Human Behavior, 2025)

Competing mechanisms for the buckling of an epithelial monolayer identified using multicellular simulation - Phillip J. Brown; J. Edward F. Green; Benjamin J. Binder; James M. Osborne (Mathematical Biosciences, 2025)

Fate of a toxic Microcystis aeruginosa bloom introduced into a subtropical estuary from a flow-managed canal and management implications - Edward J. Phlips; Susan Badylak; Eric C. Milbrandt; Benjamin Stelling; Mauricio Arias; Cassondra Armstrong; Thomas Behlmer; Amanda Chappel; Amanda Foss; David Kaplan; Leslie Landauer; Peter Landauer; et al. (Journal of Environmental Management, 2025)

Marine recreational fishery trends in total catch, catch per unit effort, and release rates in Delaware during 1981–2021 - Nicholas Whaley; Julia Fontana; Matthew Hicks; Benjamin Paul Marsaly; Timothy Smoot; Serena Bandlow; Aaron Carlisle; Edward Hale (Fisheries Management and Ecology, 2025)
The impact of recreational fisheries on marine ecosystems is often overshadowed by commercial fisheries, although recreational fishing harvest can be substantial, especially for species that are either overfished or experiencing overfishing. Delaware is a small coastal state with ~1,000,000 residents and nearly 272,000 resident and non‐resident anglers. We used publicly available data for Delaware's recreational fisheries during 1981–2021 to determine the nine most caught fish species and to evaluate trends in total numbers caught, harvested, released, and catch per unit effort (CPUE). The top nine most frequently captured fish by recreational anglers were Summer Flounder ( Paralichthys dentatus ), Atlantic Croaker ( Micropogonias undulatus ), Bluefish ( Pomatomus saltatrix ), Black Sea Bass ( Centropristis striata ), Weakfish ( Cynoscion regalis ), White Perch ( Morone americana ), Tautog ( Tautoga onitis ), Striped Bass ( Morone saxatilis ), and Spot ( Leiostomus xanthurus ). The proportion of fish released increased through time for all nine species, suggesting that the recreational fishery in Delaware is transitioning from a harvest‐oriented to a catch‐and‐release‐oriented fishery. Observations of higher release rates in recreational fisheries of Delaware are consistent with the findings elsewhere in the world for freshwater and marine systems.

Influence of regulated water discharges on phytoplankton composition and biomass in a subtropical canal - Susan Badylak; Edward J. Phlips; Eric C. Milbrandt; Elise S. Morrison; Benjamin D. Stelling; Shin-Ah Lee; Thomas A. Frankovich; David Kaplan (Journal of Environmental Management, 2025)

Interpretable machine learning tools to analyze PM2.5 sensor network data so as to quantify local source impacts and long-range transport - Benjamin de Foy; Ross Edwards; Khaled Shaifullah Joy; Shahid Uz Zaman; Abdus Salam; James J. Schauer (Atmospheric Research, 2024)

New perspectives on ice forcing in continental arc magma plumbing systems - Brad S. Singer; Pablo Moreno-Yaeger; Meredith Townsend; Christian Huber; Joshua Cuzzone; Benjamin R. Edwards; Matias Romero; Yasmeen Orellana-Salazar; Shaun A. Marcott; Rachel E. Breunig; Ken L. Ferrier; Kathryn Scholz; et al. (Journal of Volcanology and Geothermal Research, 2024)

Electrophysiological and Behavioral Responses of Cabbage Aphid (Brevicoryne brassicae) to Rosemary (Rosmarinus officinalis) Volatiles, a Potential push Plant for Vegetable push-pull Cropping System - Bretor Katuku Mutua; Thomas Dubois; Komivi Senyo Akutse; Benjamin Muli; Edward Nderitu Karanja; Daniel Munyao Mutyambai (Journal of Chemical Ecology, 2024)

Irrigation and oil palm empty fruit bunch mulch enhance eggplant growth, radiation interception and dry matter yield - John Bright Amoah Nyasapoh; Eric Oppong Danso; Daniel Selorm Kpodo; William Amponsah; Emmanuel Arthur; Edward Benjamin Sabi; Peter Bilson Obour; William Akortey; Bernard Kwabena Boadi Mensah; Grace Elorm Ayayi; Mathias Neumann Andersen (European Journal of Agronomy, 2024)

Physically adjusted ground motion prediction equations for induced seismicity at Preston New Road, UK - Pungky Megasari Suroyo; Jaleena Sunny; Benjamin Edwards (Journal of Seismology, 2024)
Predicting ground motions due to induced seismicity is a challenging task owing to the scarcity of data and heterogeneity of the uppermost crust. Dealing with this requires a thorough understanding of the underlying physics and consideration of inter-site variability. The most common ground motion model used in practice is the parametric ground motion prediction equation (GMPE), of which hundreds exist in the literature. However, relatively few are developed with a focus on induced seismicity. Developing GMPEs that are specific to an appropriate magnitude-distance range ( $$R < 30$$ R < 30 km; $$2 \le M \le 6$$ 2 ≤ M ≤ 6 ) is important for induced seismicity applications. This paper proposes a framework for the development of physically-based GMPEs to provide more accurate and reliable estimates of the potential induced-seismicity ground motion hazard, allowing for better risk assessment and management strategies. To demonstrate this approach, a new set of GMPEs for the 2018-2019 induced seismicity sequence at the Preston New Road (PNR) shale gas site near Blackpool, United Kingdom, is presented. The physically-based GMPE was developed based on a pseudo-finite-fault stochastic ground motion simulation, calibrated with parameters derived from the spectral analysis of weak-motion records from induced seismic events. An optimization-based calibration technique using the area metric (AM) was subsequently performed to calibrate optimal parameters for simulating ground motion at the PNR site. Finally, using a suite of forward simulations for events with $$1 \le M \le 6$$ 1 ≤ M ≤ 6 recorded at distances up to 30 km, combined with empirical data, a location-specific GMPE was derived through adjustment of an existing model.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Mutagenesis on a complex mouse genetic background by site-specific nucleases - Benjamin Davies; Lucy Trelfa; Victoria S. Rashbrook; Edward Drydale; Rachel Martin; Boyan Bai; Jedrzej Golebka; Daniel Stephen Biggs; Keith M. Channon; Shoumo Bhattacharya; Gillian Douglas (Transgenic Research, 2024)
Mouse models with complex genetic backgrounds are increasingly used in preclinical research to accurately model human disease and to enable temporal and cell-specific evaluation of genetic manipulations. Backcrossing mice onto these complex genetic backgrounds takes time and leads to significant wastage of animals. In this study, we aimed to evaluate whether site-specific nucleases could be used to generate additional genetic mutations in a complex genetic background, using the REVERSA mouse model of atherosclerosis, a model harbouring four genetically altered alleles. The model is comprised of a functional null mutation in the Ldlr gene in combination with a ApoB100 allele, which, after high-fat diet, leads to the rapid development of atherosclerosis. The regression of the pathology is achieved by inducible knock-out of the Mttp gene. Here we report an investigation to establish if microinjection of site-specific nucleases directly into zygotes prepared from the REVERSA could be used to investigate the role of the ATP binding cassette transporter G1 (ABCG1) in atherosclerosis regression. We show that using this approach we could successfully generate two independent knockout lines on the REVERSA background, both of which exhibited the expected phenotype of a significant reduction in cholesterol efflux to HDL in bone marrow-derived macrophages. However, loss of Abcg1 did not impact atherosclerosis regression in either the aortic root or in aortic arch, demonstrating no important role for this transporter subtype. We have demonstrated that site-specific nucleases can be used to create genetic modifications directly onto complex disease backgrounds and can be used to explore gene function without the need for laborious backcrossing of independent strains, conveying a significant 3Rs advantage.

A 561-yr (1461-2022 CE) summer temperature reconstruction for Mid-Atlantic-Northeast USA shows connections to volcanic forcing and atmospheric circulation - Grant L. Harley; Justin T. Maxwell; Karen E. King; Shelly A. Rayback; Edward R. Cook; Christopher Hansen; R. Stockton Maxwell; Frederick Reinig; Jan Esper; Tsun Fung Au; Ellen V. Bergan; Katherine E. Brings; et al. (Climatic Change, 2024)
Contextualizing current increases in Northern Hemisphere temperatures is precluded by the short instrumental record of the past ca. 120 years and the dearth of temperature-sensitive proxy records, particularly at lower latitudes south of <50 °N. We develop a network of 29 blue intensity chronologies derived from tree rings of Tsuga canadensis (L.) Carrière and Picea rubens Sarg. trees distributed across the Mid-Atlantic and Northeast USA (MANE)—a region underrepresented by multi-centennial temperature records. We use this network to reconstruct mean March-September air temperatures back to 1461 CE based on a model that explains 62% of the instrumental temperature variance from 1901−1976 CE. Since 1998 CE, MANE summer temperatures are consistently the warmest within the context of the past 561 years exceeding the 1951−1980 mean of +1.3 °C. Cool summers across MANE were frequently volcanically forced, with significant ( p <0.05) temperature departures associated with 80% of the largest tropical ( n =13) and extratropical ( n =15) eruptions since 1461 CE. Yet, we find that more of the identified cool events in the record were likely unforced by volcanism and either related to stochastic variability or atmospheric circulation via significant associations ( p <0.05) to regional, coastal sea-surface temperatures, 500-hpa geopotential height, and 300-hpa meridional and zonal wind vectors. Expanding the MANE network to the west and south and combining it with existing temperature-sensitive proxies across North America is an important next step toward producing a gridded temperature reconstruction field for North America.

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Analysis of effects and factors linked to soil microbial populations and nitrogen cycling under long-term biosolids application - Benjamin S.T. Morgan; Guanglong Tian; Olawale O. Oladeji; Albert E. Cox; Thomas C. Granato; Heng Zhang; Edward W. Podczerwinski (Science of The Total Environment, 2024)

Correction to: Drought and deluge: the recurrence of hydroclimate extremes during the past 600 years in eastern Australia’s Natural Resource Management (NRM) clusters - Jonathan G. Palmer; Danielle Verdon‑Kidd; Kathryn J. Allen; Philippa Higgins; Benjamin I. Cook; Edward R. Cook; Christian S. M. Turney; Patrick J. Baker (Natural Hazards, 2024)

Delineation of flood risk terrains and rainfall visualisation in the North Western part of Ghana - Benjamin Wullobayi Dekongmen; Amos Tiereyangn Kabo-bah; Geophrey Kwame Anornu; Komlavi Akpoti; Mark Amo-Boateng; Eric Ofosu Antwi; Edward Oppong Boamah; Emmanuel Daanoba Sunkari (Modeling Earth Systems and Environment, 2024)

Regionally adjusted stochastic earthquake ground motion models, associated variabilities and epistemic uncertainties - Jaleena Sunny; Marco de Angelis; Benjamin Edwards (Journal of Seismology, 2024)
An optimisation-based calibration technique, using the area metric, is applied to determine the input parameters of a stochastic earthquake-waveform simulation method. The calibration algorithm updates a model prior, specifically an estimate of a region’s seismological (source, path and site) parameters, typically developed using waveform data, or existing models, from a wide range of sources. In the absence of calibration, this can result in overestimates of a target region’s ground motion variability, and in some cases, introduce biases. The proposed method simultaneously attains optimum estimates of median, range and distribution (uncertainty) of these seismological parameters, and resultant ground motions, for a specific target region, through calibration of physically constrained parametric models to local ground motion data. We apply the method to Italy, a region of moderate seismicity, using response spectra recorded in the European Strong Motion (ESM) dataset. As a prior, we utilise independent seismological models developed using strong motion data across a wider European context. The calibration obtains values of each seismological parameter considered (such as, but not limited to, quality factor, geometrical spreading and stress drop), to develop a suite of optimal parameters for locally adjusted stochastic ground motion simulation. We consider both the epistemic and aleatory variability associated with the calibration process. We were able to reduce the area metric (misfit) value by up to 88% for the simulations using updated parameters, compared to the initial prior. This framework for the calibration and updating of seismological models can help achieve robust and transparent regionally adjusted estimates of ground motion, and to consider epistemic uncertainty through correlated parameters.

The role of living labs in cultivating inclusive and responsible innovation in precision agriculture - Maaz Gardezi; Halimeh Abuayyash; Paul R. Adler; Juan P. Alvez; Rubaina Anjum; Appala Raju Badireddy; Skye Brugler; Pablo Carcamo; David Clay; Ali Dadkhah; Mary Emery; Joshua W. Faulkner; et al. (Agricultural Systems, 2024)

Delayed leaf greening involves a major shift in the expression of cytosolic and mitochondrial ribosomes to plastid ribosomes in the highly phosphorus-use-efficient Hakea prostrata (Proteaceae) - Toby Bird; Benjamin J. Nestor; Philipp E. Bayer; Guannan Wang; Albina Ilyasova; Clément E. Gille; Bryce E. H. Soraru; Kosala Ranathunge; Anita A. Severn-Ellis; Ricarda Jost; Wolf-Rüdiger Scheible; Maheshi Dassanayake; et al. (Plant and Soil, 2024)
Background and aims Hakea prostrata (Proteaceae) is a highly phosphorus-use-efficient plant native to southwest Australia. It maintains a high photosynthetic rate at low leaf phosphorus (P) and exhibits delayed leaf greening, a convergent adaptation that increases nutrient-use efficiency. This study aimed to provide broad physiological and gene expression profiles across leaf development, uncovering pathways leading from young leaves as nutrient sinks to mature leaves as low-nutrient, energy-transducing sources. Methods To explore gene expression underlying delayed greening, we analysed a de novo transcriptome for H. prostrata across five stages of leaf development. Photosynthesis and respiration rates, and foliar pigment, P and nitrogen (N) concentrations were determined, including the division of P into five biochemical fractions. Key results Transcripts encoding functions associated with leaf structure generally decreased in abundance across leaf development, concomitant with decreases in foliar concentrations of 85% for anthocyanins, 90% for P and 70% for N. The expression of genes associated with photosynthetic function increased during or after leaf expansion, in parallel with increases in photosynthetic pigments and activity, much later in leaf development than in species that do not have delayed greening. As leaves developed, transcript abundance for cytosolic and mitochondrial ribosomal proteins generally declined, whilst transcripts for chloroplast ribosomal proteins increased. Conclusions There was a much longer temporal separation of leaf cell growth from chloroplast development in H. prostrata than is found in species that lack delayed greening. Transcriptome-guided analysis of leaf development in H. prostrata provided insight into delayed greening as a nutrient-saving strategy in severely phosphorus-impoverished landscapes.

Drought and deluge: the recurrence of hydroclimate extremes during the past 600 years in eastern Australia’s Natural Resource Management (NRM) clusters - Jonathan G. Palmer; Danielle Verdon-Kidd; Kathryn J. Allen; Philippa Higgins; Benjamin I. Cook; Edward R. Cook; Christian S. M. Turney; Patrick J. Baker (Natural Hazards, 2024)
Recent extremes of flood and drought across Australia have raised questions about the recurrence of such rare events and highlighted the importance of understanding multi-decadal climate variability. However, instrumental records over the past century are too short to adequately characterise climate variability on multi-decadal and longer timescales or robustly determine extreme event frequencies and their duration. Palaeoclimate reconstructions can provide much-needed information to help address this problem. Here, we use the 600-year hydroclimate record captured in the eastern Australian and New Zealand Drought Atlas (ANZDA) to analyse drought and pluvial frequency trends for East Australian Natural Resource Management (NRM) clusters. This partitioning of the drought atlas grid points into recognised biophysical areas (i.e. NRM clusters) revealed their differences and similarities in drought intensity and pluvial events over time. We find sustained multi-decadal periods of a wet–dry geographic 'seesaw' between eastern to central and southern NRMs (e.g. 1550–1600 CE and 1700–1750 CE). In contrast, other periods reveal spatially consistent wetting (e.g. 1500–1550 CE) or drying (e.g. 1750–1800 CE). Emerging hot spot analysis further shows that some areas that appear naturally buffered from severe drought during the instrumental period have a greater exposure risk when the longer 600-year record is considered. These findings are particularly relevant to management plans when dealing with the impacts of climate extremes developed at regional scales. Our results demonstrate that integrating and extending instrumental records with palaeoclimate datasets will become increasingly important for developing robust and locally specific extreme event frequency information for managing water resources.

Canola meal as a supplement for grass-fed beef cattle: Effects on growth rates, carcase and meat quality, and consumer sensory evaluations - Emma E.M. Lynch; Edward H. Clayton; Benjamin W.B. Holman; David L. Hopkins; Rod J. Polkinghorne; Michael A. Campbell (Meat Science, 2024)

Design Update to “The Pressure of In-Situ Gases Instrument (PIGI) for Autonomous Shipboard Measurement of Dissolved O2 and N2 in Surface Ocean Waters” - Benjamin Lowin; Robert Izett; Edward Taylor; Charles Robertson; Sara Rivero-Calle (Oceanography, 2024)
Measuring net community production (NCP) is a challenging, yet important, aspect of oceanography. Methods based on discrete sample collection often have low spatial and temporal resolution, while expensive instruments are required to obtain continuous NCP measurements at high resolution. To address these issues, Izett and Tortell (2020) created a novel, autonomous system called the Pressure of In-situ Gases Instrument (PIGI) and shared their design with the community. The system yields high-resolution surface water O2 and N2 measurements that are used to estimate NCP along a ship transect or at a fixed field station. This article provides a description of an updated PIGI system that was tested in a series of cruises in the coastal South Atlantic Bight (SAB). The data collected suggest that it performs equally as well as the original, providing high spatial resolution NCP measurements. Unfortunately, we believe that the SAB coastal and estuaries violate the steady state assumption due to horizontal mixing driven by tidal forces. Thus, we cannot recommend the PIGI system for use in the coastal SAB, but we encourage its use in open ocean waters that do not violate the assumptions on which this system was built. We document the updates to the PIGI system, share tips and tricks on its use, and discuss the data collected.

Approaches to increase the validity of gene family identification using manual homology search tools - Benjamin J. Nestor; Philipp E. Bayer; Cassandria G. Tay Fernandez; David Edwards; Patrick M. Finnegan (Genetica, 2023)
Identifying homologs is an important process in the analysis of genetic patterns underlying traits and evolutionary relationships among species. Analysis of gene families is often used to form and support hypotheses on genetic patterns such as gene presence, absence, or functional divergence which underlie traits examined in functional studies. These analyses often require precise identification of all members in a targeted gene family. Manual pipelines where homology search and orthology assignment tools are used separately are the most common approach for identifying small gene families where accurate identification of all members is important. The ability to curate sequences between steps in manual pipelines allows for simple and precise identification of all possible gene family members. However, the validity of such manual pipeline analyses is often decreased by inappropriate approaches to homology searches including too relaxed or stringent statistical thresholds, inappropriate query sequences, homology classification based on sequence similarity alone, and low-quality proteome or genome sequences. In this article, we propose several approaches to mitigate these issues and allow for precise identification of gene family members and support for hypotheses linking genetic patterns to functional traits.

Distinct dynamics of plant- and microbial-derived soil organic matter in relation to varying climate and soil properties in temperate agroecosystems - Meiling Man; Edward G. Gregorich; Michael H. Beare; Benjamin H. Ellert; Myrna J. Simpson (Geochimica et Cosmochimica Acta, 2023)

Improving photosynthetic efficiency toward food security: Strategies, advances, and perspectives - Edward N. Smith; Marvin van Aalst; Tiina Tosens; Ülo Niinemets; Benjamin Stich; Tomas Morosinotto; Alessandro Alboresi; Tobias J. Erb; Paul A. Gómez-Coronado; Dimitri Tolleter; Giovanni Finazzi; Gilles Curien; et al. (Molecular Plant, 2023)

Impact of the antibiotic doxycycline on the D. magna reproduction, associated microbiome and antibiotic resistance genes in treated wastewater conditions - Maria Paula Carrillo; Marina Sevilla; Marta Casado; Benjamin Piña; Edward Pastor López; Victor Matamoros; Maria Vila-Costa; Carlos Barata (Environmental Pollution, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Internal endpoint temperature (level of cooking doneness) effects on the fatty acid and mineral profiles of grilled lamb m. longissimus lumborum - Benjamin W.B. Holman; Stephanie M. Fowler; Kristy L. Bailes; Richard G. Meyer; David L. Hopkins; Edward H. Clayton (Meat Science, 2023)

Fungal symbiont community and absence of detectable mycangia in invasive Euplatypus ambrosia beetles - Andre Rodrigues; Andrew J. Johnson; Ross A. Joseph; You Li; Nemat O. Keyhani; Edward L. Stanley; Benjamin Weiss; Martin Kaltenpoth; Matthew E. Smith; Jiri Hulcr (Symbiosis, 2023)

Tono basin climate modeling, the potential advantage of fully coupled WRF/WRF-Hydro modeling System - Edward Naabil; Kouakou Kouadio; Benjamin Lamptey; Thompson Annor; Ifeanyi Chukwudi Achugbu (Modeling Earth Systems and Environment, 2023)

Phenotypic variation in the molt characteristics of a seasonal coat color-changing species reveals limited resilience to climate change - Taylor R. Peltier; Shotaro Shiratsuru; Benjamin Zuckerberg; Mark Romanski; Lynette Potvin; Andrew Edwards; Jonathan H. Gilbert; Tanya R. Aldred; Ann Dassow; Jonathan N. Pauli (Oecologia, 2023)

Carbon acquisition ecological strategies to connect soil microbial biodiversity and carbon cycling - Ember M. Morrissey; Jennifer Kane; Binu M. Tripathi; Md Shafiul Islam Rion; Bruce A. Hungate; Rima Franklin; Chris Walter; Benjamin Sulman; Edward Brzostek (Soil Biology and Biochemistry, 2023)

CRISPR-knockout of β-kafirin in sorghum does not recapitulate the grain quality of natural mutants - Karen Massel; Jessica Hintzsche; Jemma Restall; Edward D. Kerr; Benjamin L. Schulz; Ian D. Godwin (Planta, 2023)

Lava-ice interactions during historical eruptions of Veniaminof Volcano, Alaska and the potential for meltwater floods and lahars - Christopher F. Waythomas; Benjamin R. Edwards; Thomas P. Miller; Robert G. McGimsey (Natural Hazards, 2023)
Veniaminof Volcano on the Alaska Peninsula of southwest Alaska is one of a small group of ice-clad volcanoes globally that erupts lava flows in the presence of glacier ice. Here, we describe the nature of lava-ice-snow interactions that have occurred during historical eruptions of the volcano since 1944. Lava flows with total volumes on the order of 0.006 km 3 have been erupted in 1983–1984, 1993–1994, 2013, and 2018. Smaller amounts of lava (1 × 10 −4 km 3 or less) were generated during eruptions in 1944 and 2021. All known historical eruptions have occurred at a 300-m-high cinder cone (informally named cone A) within the 8 × 10-km-diameter ice-filled caldera that characterizes Veniaminof Volcano. Supraglacial lava flows erupted at cone A, resulted in minor amounts of melting and did not lead to any significant outflows of water in nearby drainages. Subglacial effusion of lava in 1983–1984, 2021 and possibly in 1944 and 1993–1994 resulted in more significant melting including a partially water-filled melt pit, about 0.8 km 2 in area, that developed during the 1983–1984 eruption. The 1983–1984 event created an impression that meltwater floods from Mount Veniaminof’s ice-filled caldera could be significant and hazardous given the large amount of glacier ice resident within the caldera (ice volume about 8 km 3 ). To date, no evidence supporting catastrophic outflow of meltwater from lava-ice interactions at cone A has been found. Analysis of imagery from the 1983–1984 eruption shows that the initial phase erupted englacial lavas that melted ice/snow/firn from below, producing surface subsidence outward from the cone with no discernable surface connection to the summit vent on cone A. This also happened during the 2021 eruption, and possibly during the 1993–1994 eruption although meltwater lakes did not form during these events. Thus, historical eruptions at Veniaminof Volcano appear to have two different modes of effusive eruptive behavior, where lava reaches the ice subglacially from flank vents, or where lava flows are erupted subaerially from vents near the summit of cone A and flow down the cone on to the ice surface. When placed in the context of global lava-ice eruptions, in cases where lava flows melt the ice from the surface downward, the main hazards are from localized phreatic explosions as opposed to potential flood/lahar hazards. However, when lava effusion/emplacement occurs beneath the ice surface, melting is more rapid and can produce lakes whose drainage could plausibly produce localized floods and lahars.

A Low-Cost, DIY Ultrasonic Water Level Sensor for Education, Citizen Science, and Research - Philip Bresnahan; Ellen Briggs; Benjamin Davis; Angelica Rodriguez; Luke Edwards; Cheryl Peach; Nan Renner; Harry Helling; Mark Merrifield (Oceanography, 2023)
A low-cost (~$100), do-it-yourself (DIY) ultrasonic water level sensor/datalogger has been designed, constructed, and tested for use in education, citizen/community science, and research settings. The sensor package comprises an ultrasonic distance sensor, a microcontroller running Arduino firmware, a micro-SD card for datalogging, a real-time clock for timekeeping and sleep functions, and an OLED screen for real-time display. Electronics are housed in low-cost custom containers using either upcycled plastic containers or laser-cut acrylic. Reported ultrasonic sensor accuracy is 5 cm across a range of 15–645 cm, with an estimated power budget of 76 days of operation on a rechargeable 10 amp-hr battery. The DIY sensor has been field tested alongside two commercial sensors for 18 days in Wilmington, North Carolina, including during Tropical Storm Colin, with all sensor measurements in close agreement (e.g., root mean squared error of 1.5 cm between the DIY sensor and a proven commercial unit). Potential applications, design and construction, and deployment recommendations for the sensors are described, as well as simple and inexpensive modifications to the sensor and its packaging that could further improve performance. Preliminary lesson plans written to accompany the device for high school- and undergraduate-level educational projects are available.

Ground-motion prediction models for induced earthquakes in the Groningen gas field, the Netherlands - Julian J. Bommer; Peter J. Stafford; Elmer Ruigrok; Adrian Rodriguez-Marek; Michail Ntinalexis; Pauline P. Kruiver; Benjamin Edwards; Bernard Dost; Jan van Elk (Journal of Seismology, 2022)
Small-magnitude earthquakes induced by gas production in the Groningen field in the Netherlands have prompted the development of seismic risk models that serve both to estimate the impact of these events and to explore the efficacy of different risk mitigation strategies. A core element of the risk modelling is ground-motion prediction models (GMPM) derived from an extensive database of recordings obtained from a dense network of accelerographs installed in the field. For the verification of damage claims, an empirical GMPM for peak ground velocity (PGV) has been developed, which predicts horizontal PGV as a function of local magnitude, M L ; hypocentral distance, R hyp ; and the time-averaged shear-wave velocity over the upper 30 m, V S30 . For modelling the risk due to potential induced and triggered earthquakes of larger magnitude, a GMPM for response spectral accelerations has been developed from regressions on the outputs from finite-rupture simulations of motions at a deeply buried rock horizon. The GMPM for rock motions is coupled with a zonation map defining frequency-dependent non-linear amplification factors to obtain estimates of surface motions in the region of thick deposits of soft soils. The GMPM for spectral accelerations is formulated within a logic-tree framework to capture the epistemic uncertainty associated with extrapolation from recordings of events of M L ≤ 3.6 to much larger magnitudes.

Can Soluble Immune Checkpoint Molecules on Exosomes Mediate Inflammation? - Julie Joseph; Benjamin Rahmani; Yonesha Cole; Neha Puttagunta; Edward Lin; Zafar K. Khan; Pooja Jain (Journal of Neuroimmune Pharmacology, 2022)

Blood in the water: DNA barcoding of traded shark fins in Singapore - Lynn Drescher; Noel Jin Kiat Heng; Min Yi Chin; Neel R. O. Karve; Edward Jun Wei Cheung; Anastasia Kurniadi; Mariana Quesada Urera; Felipe Gabriel Waldeck; U. Dharshini; Nirel Tze En Hoe; Joshua Song Yang Choo; Russell Fock Jun Lok; et al. (Frontiers in Marine Science, 2022)
Overfishing has significantly decreased global shark populations, with some species experiencing reductions of approximately 70% over the last 50 years. Singapore is a major shark fin transhipment hub that helps to satisfy the global demand for shark fins, which are considered status symbols and reputed to have medicinal value in Asian culture. Despite the recognised and urgent need to better protect shark populations, the success of such efforts has been limited by the difficulties associated with visually identifying the species of shark from which the fins originated. In this study, we collected 451 shark fin tissue samples from a variety of local retail markets in Singapore. Using DNA barcoding techniques, we amplified a 350 base pair fragment of the mitochondrial cytochrome c oxidase subunit I (COI) gene from each to identify the species sold in Singapore. We identified 22 shark species, of which 17 are categorised as Threatened (Critically Endangered, Endangered or Vulnerable) under the IUCN Red List. Six of these species are also listed on Appendix II of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES).

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Importance of equitable cost sharing in the Convention on Biological Diversity's protected area agenda - Keila Stark; Vanessa Adams; Christopher J. Brown; Alienor Chauvenet; Katrina Davis; Edward T. Game; Benjamin S. Halpern; John Lynham; Bonnie Mappin; Kim Selkoe; James E. M. Watson; Hugh P. Possingham; et al. (Conservation Biology, 2022)

Changing hydroclimate dynamics and the 19th to 20th century wetting trend in the English Channel region of northwest Europe - Serena R. Scholz; Richard Seager; Mingfang Ting; Yochanan Kushnir; Jason E. Smerdon; Benjamin I. Cook; Edward R. Cook; Seung Hun Baek (Climate Dynamics, 2022)

Aspirin use and prostate tumor angiogenesis - Benjamin C. Fu; Kai Wang; Lorelei A. Mucci; Steven K. Clinton; Edward L. Giovannucci (Cancer Causes & Control, 2022)

Induced seismicity due to hydraulic fracturing near Blackpool, UK: source modeling and event detection - Nasim Karamzadeh; Mike Lindner; Benjamin Edwards; Emmanuel Gaucher; Andreas Rietbrock (Journal of Seismology, 2021)
Monitoring small magnitude induced seismicity requires a dense network of seismic stations and high-quality recordings in order to precisely determine events’ hypocentral parameters and mechanisms. However, microseismicity (e.g. swarm activity) can also occur in an area where a dense network is unavailable and recordings are limited to a few seismic stations at the surface. In this case, using advanced event detection techniques such as template matching can help to detect small magnitude shallow seismic events and give insights about the ongoing process at the subsurface giving rise to microseismicity. In this paper, we study shallow microseismic events caused by hydrofracking of the PNR-2 well near Blackpool, UK, in 2019 using recordings of a seismic network which was not designed to detect and locate such small events. By utilizing a sparse network of surface stations, small seismic events are detected using template matching technique. In addition, we apply a full-waveform moment tensor inversion to study the focal mechanisms of larger events ( M L > 1) and used the double-difference location technique for events with high-quality and similar waveforms to obtain accurate relative locations. During the stimulation period, temporal changes in event detection rate were in agreement with injection times. Focal mechanisms of the events with high-quality recordings at multiple stations indicate a strike-slip mechanism, while a cross-section of 34 relocated events matches the dip angle of the active fault.

Does Biochar Particle Size, Application Rate and Irrigation Regime Interact to Affect Soil Water Holding Capacity, Maize Growth and Nutrient Uptake? - Eric Oppong Danso; Francis Monnie; Stephen Abenney-Mickson; Emmanuel Arthur; Edward Benjamin Sabi; Mathias Neumann Andersen (Journal of Soil Science and Plant Nutrition, 2021)

Defining the usable bandwidth of weak-motion records: application to induced seismicity in the Groningen Gas Field, the Netherlands - Benjamin Edwards; Michail Ntinalexis (Journal of Seismology, 2021)
Seismic hazard and risk analyses are increasingly tapping into the previously underused resource of local weak-motion records. This is facilitating the development of local- or even application-specific models for the characterisation of earthquake ground motion. In turn, this offers the opportunity to derive non- or partially non-ergodic models and significantly reduce bias and uncertainty. However, weak-motion data, while carrying important information about local earthquake source, path and site effects, are susceptible to noise. We show that high-frequency noise has a record-, or region-specific, impact on pseudo-spectral acceleration (PSA). This impact depends on the shape of the records’ Fourier amplitude spectrum (FAS): PSA from moderately to highly damped ‘soil’ records (e.g. Groningen, the Netherlands) is much less susceptible to high-frequency noise than PSA from weakly damped ‘rock’ records (e.g. Eastern North America). We make use of simulated ground motion records to develop a parametric model for the lower usable period of PSA ( T min ). The model accounts for the impact of high-frequency noise on PSA, conditional on easily measured parameters characterising the shape of a record’s FAS. We then present a workflow, describing processing undertaken for records of induced seismicity from the Groningen gas field. The workflow includes the definition of maximum and minimum usable frequencies and periods of FAS and PSA, respectively. As part of the workflow, we present an approach that considers multiple estimates of T min . These include the parametric model and, additionally, record-specific hybrid simulations that artificially extend or modify time series’ FAS beyond the noise floor to assess subsequent impacts on PSA.

Scenarios for Global Aquaculture and Its Role in Human Nutrition - Jessica A. Gephart; Christopher D. Golden; Frank Asche; Ben Belton; Cecile Brugere; Halley E. Froehlich; Jillian P. Fry; Benjamin S. Halpern; Christina C. Hicks; Robert C. Jones; Dane H. Klinger; David C. Little; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

An agenda for ethics and justice in adaptation to climate change - Morten Fibieger Byskov; Keith Hyams; Poshendra Satyal; Isabelle Anguelovski; Lisa Benjamin; Sophie Blackburn; Maud Borie; Simon Caney; Eric Chu; Gareth Edwards; Kristel Fourie; Arabella Fraser; et al. (Climate and Development, 2021)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Macroalgal defense phenotype correlates with herbivore abundance - Scott S. Gabara; Benjamin P. Weitzman; Brenda H. Konar; Matthew S. Edwards (Marine Biology, 2020)

A Bornean peat swamp forest is a net source of carbon dioxide to the atmosphere - Angela C. I. Tang; Lulie Melling; Paul C. Stoy; Kevin K. Musin; Edward B. Aeries; Joseph W. Waili; Mariko Shimizu; Benjamin Poulter; Ryuichi Hirata (Global Change Biology, 2020)
Tropical peat forests are a globally important reservoir of carbon, but little is known about CO 2 exchange on an annual basis. We measured CO 2 exchange between the atmosphere and tropical peat swamp forest in Sarawak, Malaysia using the eddy covariance technique over 4 years from 2011 to 2014. The CO 2 fluxes varied between seasons and years. A small carbon uptake took place during the rainy season at the beginning of 2011, while a substantial net efflux of >600 g C/m 2 occurred over a 2 month period in the middle of the dry season. Conversely, the peat ecosystem was a source of carbon during both the dry and rainy seasons in subsequent years and more carbon was lost during the rainy season relative to the dry season. Our results demonstrate that the forest was a net source of CO 2 to the atmosphere during every year of measurement with annual efflux ranging from 183 to 632 g C m −2 year −1 , noting that annual flux values were sensitive to gap filling methodology. This is in contrast to the typical view of tropical peat forests which must have acted as net C sinks over time scales of centuries to millennia to create the peat deposits. Path analyses revealed that the gross primary productivity (GPP) and ecosystem respiration (RE) were primarily affected by vapour pressure deficit (VPD). Results suggest that future increases in VPD could further reduce the C sink strength and result in additional net CO 2 losses from this tropical peat swamp forest in the absence of plant acclimation to such changes in atmospheric dryness.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Nutritional factors modulating plant and fruit susceptibility to pathogens: BARD workshop, Haifa, Israel, February 25–26, 2018 - Dov Prusky; Leandro José de Assis; Riccardo Baroncelli; Ernesto P. Benito; Virginia Casado del Castillo; Timothy Chaya; Shay Covo; José María Díaz-Mínguez; Nicole M. Donofrio; Eduardo Espeso; Tânia Ribeiro Fernandes; Gustavo H. Goldman; et al. (Phytoparasitica, 2020)

The Antarctic Ice Sheet: A Paleoclimate Modeling Perspective - Edward Gasson; Benjamin Keisling (Oceanography, 2020)

The European Russia Drought Atlas (1400–2016 CE) - Edward R. Cook; Olga Solomina; Vladimir Matskovsky; Benjamin I. Cook; Leonid Agafonov; Alina Berdnikova; Ekaterina Dolgova; Aleksey Karpukhin; Natallia Knysh; Marina Kulakova; Veronika Kuznetsova; Tomáš Kyncl; et al. (Climate Dynamics, 2020)

Nitric oxide mediates oxylipin production and grazing defense in diatoms - Matthew D. Johnson; Bethanie R. Edwards; David J. Beaudoin; Benjamin A. S. Van Mooy; Assaf Vardi (Environmental Microbiology, 2020)
Summary Diatom blooms are important features of productive marine ecosystems and are known to support higher trophic levels. However, when stressed or wounded, diatoms can produce oxylipin molecules known to inhibit the reproduction and development of copepods and decrease microzooplankton growth rates. Using oxylipin chemical treatments, lipidomic analysis and functional genomic approaches, we provide evidence that nitric oxide (NO) and oxylipin signalling pathways in diatoms respond to protist grazers, resulting in increased defence fitness and survival. Exposure of the diatom Phaeodactylum tricornutum to the dinoflagellate Oxyrrhis marina resulted in NO production by P . tricornutum and pronounced change in its dissolved oxylipin profile. Experimentally elevating levels of NO also resulted in increased oxylipin production, and lower overall grazing rates. Furthermore, O . marina preferentially grazed on P . tricornutum prey with lower levels of NO, suggesting that this molecule and its effect on oxylipin pathways play a key role in prey selection. Exposure of O . marina grazing on P . tricornutum to exogenous oxylipins also decreased grazing rates, which is consistent with a grazing deterrence role for these molecules. These results suggest that NO and oxylipin production help to structure diatom communities, in part by modulating interactions with microzooplankton predators.

Ground-motion networks in the Groningen field: usability and consistency of surface recordings - Michail Ntinalexis; Julian J. Bommer; Elmer Ruigrok; Benjamin Edwards; Rui Pinho; Bernard Dost; António A. Correia; Jeroen Uilenreef; Peter J. Stafford; Jan van Elk (Journal of Seismology, 2019)
Several strong-motion networks have been installed in the Groningen gas field in the Netherlands to record ground motions associated with induced earthquakes. There are now more than 450 permanent surface accelerographs plus a mobile array of 450 instruments, which, in addition to many instrumented boreholes, yield a wealth of data. The database of recordings has been of fundamental importance to the development of ground-motion models that form a key element of the seismic hazard and risk estimations for the field. In order to maximise the benefit that can be derived from these recordings, this study evaluates the usability of the recordings from the different networks, in general terms and specifically with regards to the frequency ranges with acceptable signal-to-noise ratios. The study also explores the consistency among the recordings from the different networks, highlighting in particular how a configuration error was identified and resolved. The largest accelerograph network consists of instruments housed in buildings around the field, frequently installed on the lower parts of walls rather than on the floor. A series of experiments were conducted, using additional instruments installed adjacent to these buildings and replicating the installation configuration in full-scale shake table tests, to identify the degree to which structural response contaminated the recordings. The general finding of these efforts was that for PGV and oscillator periods above 0.1 s, the response spectral ordinates from these recordings can be used with confidence.

Ocean Energy Systems Wave Energy Modelling Task: Modelling, Verification and Validation of Wave Energy Converters - Fabian Wendt; Kim Nielsen; Yi-Hsiang Yu; Harry Bingham; Claes Eskilsson; Morten Kramer; Aurélien Babarit; Tim Bunnik; Ronan Costello; Sarah Crowley; Benjamin Gendron; Giuseppe Giorgi; et al. (Journal of Marine Science and Engineering, 2019)
The International Energy Agency Technology Collaboration Programme for Ocean Energy Systems (OES) initiated the OES Wave Energy Conversion Modelling Task, which focused on the verification and validation of numerical models for simulating wave energy converters (WECs). The long-term goal is to assess the accuracy of and establish confidence in the use of numerical models used in design as well as power performance assessment of WECs. To establish this confidence, the authors used different existing computational modelling tools to simulate given tasks to identify uncertainties related to simulation methodologies: (i) linear potential flow methods; (ii) weakly nonlinear Froude–Krylov methods; and (iii) fully nonlinear methods (fully nonlinear potential flow and Navier–Stokes models). This article summarizes the code-to-code task and code-to-experiment task that have been performed so far in this project, with a focus on investigating the impact of different levels of nonlinearities in the numerical models. Two different WECs were studied and simulated. The first was a heaving semi-submerged sphere, where free-decay tests and both regular and irregular wave cases were investigated in a code-to-code comparison. The second case was a heaving float corresponding to a physical model tested in a wave tank. We considered radiation, diffraction, and regular wave cases and compared quantities, such as the WEC motion, power output and hydrodynamic loading.

Ten tips for developing interdisciplinary socio-ecological researchers - Rachel Kelly; Mary Mackay; Kirsty L. Nash; Christopher Cvitanovic; Edward H. Allison; Derek Armitage; Aletta Bonn; Steven J. Cooke; Stewart Frusher; Elizabeth A. Fulton; Benjamin S. Halpern; Priscila F. M. Lopes; et al. (Socio-Ecological Practice Research, 2019)

Modeling Temperature Regime and Physical Habitat Impacts from Restored Streamflow - Russell T. Bair; Benjamin W. Tobin; Brian D. Healy; Claire E. Spangenberg; Hampton K. Childres; Edward R. Schenk (Environmental Management, 2019)

Development of community of practice to support quantitative risk assessment for synthetic biology products: contaminant bioremediation and invasive carp control as cases - Benjamin D. Trump; Christy Foran; Taylor Rycroft; Matthew D. Wood; Nirzwan Bandolin; Mariana Cains; Timothy Cary; Fiona Crocker; Nicholas A. Friedenberg; Patrick Gurian; Kerry Hamilton; Jan Jeffrey Hoover; et al. (Environment Systems and Decisions, 2018)

Decline in Ecosystem δ13C and Mid-Successional Nitrogen Loss in a Two-Century Postglacial Chronosequence - Edward T. Malone; Benjamin W. Abbott; Megan J. Klaar; Chris Kidd; Mathieu Sebilo; Alexander M. Milner; Gilles Pinay (Ecosystems, 2018)

Modeling marine pelagic fish species spatiotemporal distributions utilizing a maximum entropy approach - Lifei Wang; Lisa A. Kerr; Nicholas R. Record; Eric Bridger; Benjamin Tupper; Katherine E. Mills; Edward M. Armstrong; Andrew J. Pershing (Fisheries Oceanography, 2018)
Understanding how ocean conditions influence fish distributions is critical for elucidating the role of climate in ecosystem change and forecasting how fish may be distributed in the future. Traditional species distribution models are often applied to scientific‐survey data, which include species presence‐absence information, to predict distributions. Maximum entropy (MaxEnt) models are promising tools as they can be applied to presence‐only data (e.g., data collected from fishermen targeting a specific species or from observers in citizen‐science programs). We used MaxEnt models to relate occurrence records of three marine pelagic fish (Atlantic herring, Atlantic mackerel, and butterfish) in fishery‐dependent data to environmental conditions (sea surface temperature ( SST ) and chlorophyll‐ a concentration from satellite remote sensing, bathymetry, and climate indices), and evaluated model performance by both cross‐validation and validation using fishery‐independent data. We developed monthly habitat suitability maps for these fish in the Northwest Atlantic Shelf area, and assessed the relative influence of environmental factors on their distributions. Across months, their suitable habitat areas varied with each species exhibiting inshore‐offshore and north‐south movements in response to changing environmental conditions. Overall, SST and chlorophyll‐ a concentration had the greatest influence on the distributions of these fish, with bathymetry having moderate influence and climate indices having little influence. Our application of MaxEnt models enabled us to integrate presence‐only data and high resolution environmental data from satellite remote sensing to describe spatiotemporal distributions of marine pelagic fish. These models were used to hindcast species occurrence in relation to historical environmental conditions to evaluate their predictive performance, and have the potential to provide nowcasts in relation to current conditions or forecasts of species future distributions.

Comparative, collaborative, and integrative risk governance for emerging technologies - Igor Linkov; Benjamin D. Trump; Elke Anklam; David Berube; Patrick Boisseasu; Christopher Cummings; Scott Ferson; Marie-Valentine Florin; Bernard Goldstein; Danail Hristozov; Keld Alstrup Jensen; Georgios Katalagarianakis; et al. (Environment Systems and Decisions, 2018)

Characterisation of ground motion recording stations in the Groningen gas field - Rik Noorlandt; Pauline P. Kruiver; Marco P. E. de Kleine; Marios Karaoulis; Ger de Lange; Antonio Di Matteo; Julius von Ketelhodt; Elmer Ruigrok; Benjamin Edwards; Adrian Rodriguez-Marek; Julian J. Bommer; Jan van Elk; et al. (Journal of Seismology, 2018)

Review: The distribution, flow, and quality of Grand Canyon Springs, Arizona (USA) - Benjamin W. Tobin; Abraham E. Springer; David K. Kreamer; Edward Schenk (Hydrogeology Journal, 2018)

Importance of Consistent Datasets in Musculoskeletal Modelling: A Study of the Hand and Wrist - Benjamin Goislard De Monsabert; Dafydd Edwards; Darshan Shah; Angela Kedgley (Annals of Biomedical Engineering, 2018)

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Stochastic source, path and site attenuation parameters and associated variabilities for shallow crustal European earthquakes - Sanjay Singh Bora; Fabrice Cotton; Frank Scherbaum; Benjamin Edwards; Paola Traversa (Bulletin of Earthquake Engineering, 2017)

Extreme climatic conditions and health service utilisation across rural and metropolitan New South Wales - Edward Jegasothy; Rhydwyn McGuire; John Nairn; Robert Fawcett; Benjamin Scalley (International Journal of Biometeorology, 2017)

Establishing the link between market orientation and agricultural commercialization: Empirical evidence from Northern Ghana - Edward Martey; Prince M. Etwire; Alexander Nimo Wiredu; Benjamin D. K. Ahiabor (Food Security, 2017)

Feedbacks between plant N demand and rhizosphere priming depend on type of mycorrhizal association - Benjamin N. Sulman; Edward R. Brzostek; Chiara Medici; Elena Shevliakova; Duncan N. L. Menge; Richard P. Phillips (Ecology Letters, 2017)
Ecosystem carbon (C) balance is hypothesised to be sensitive to the mycorrhizal strategies that plants use to acquire nutrients. To test this idea, we coupled an optimality‐based plant nitrogen (N) acquisition model with a microbe‐focused soil organic matter ( SOM ) model. The model accurately predicted rhizosphere processes and C–N dynamics across a gradient of stands varying in their relative abundance of arbuscular mycorrhizal ( AM ) and ectomycorrhizal ( ECM ) trees. When mycorrhizal dominance was switched – ECM trees dominating plots previously occupied by AM trees, and vice versa – legacy effects were apparent, with consequences for both C and N stocks in soil. Under elevated productivity, ECM trees enhanced decomposition more than AM trees via microbial priming of unprotected SOM . Collectively, our results show that ecosystem responses to global change may hinge on the balance between rhizosphere priming and SOM protection, and highlight the importance of dynamically linking plants and microbes in terrestrial biosphere models.

Litter decay controlled by temperature, not soil properties, affecting future soil carbon - Edward G. Gregorich; Henry Janzen; Benjamin H. Ellert; Bobbi L. Helgason; Budong Qian; Bernie J. Zebarth; Denis A. Angers; Ronald P. Beyaert; Craig F. Drury; Scott D. Duguid; William E. May; Brian G. McConkey; et al. (Global Change Biology, 2017)
Widespread global changes, including rising atmospheric CO 2 concentrations, climate warming and loss of biodiversity, are predicted for this century; all of these will affect terrestrial ecosystem processes like plant litter decomposition. Conversely, increased plant litter decomposition can have potential carbon‐cycle feedbacks on atmospheric CO 2 levels, climate warming and biodiversity. But predicting litter decomposition is difficult because of many interacting factors related to the chemical, physical and biological properties of soil, as well as to climate and agricultural management practices. We applied 13 C‐labelled plant litter to soil at ten sites spanning a 3500‐km transect across the agricultural regions of Canada and measured its decomposition over five years. Despite large differences in soil type and climatic conditions, we found that the kinetics of litter decomposition were similar once the effect of temperature had been removed, indicating no measurable effect of soil properties. A two‐pool exponential decay model expressing undecomposed carbon simply as a function of thermal time accurately described kinetics of decomposition. ( R 2 = 0.94; RMSE = 0.0508). Soil properties such as texture, cation exchange capacity, pH and moisture, although very different among sites, had minimal discernible influence on decomposition kinetics. Using this kinetic model under different climate change scenarios, we projected that the time required to decompose 50% of the litter (i.e. the labile fractions) would be reduced by 1–4 months, whereas time required to decompose 90% of the litter (including recalcitrant fractions) would be reduced by 1 year in cooler sites to as much as 2 years in warmer sites. These findings confirm quantitatively the sensitivity of litter decomposition to temperature increases and demonstrate how climate change may constrain future soil carbon storage, an effect apparently not influenced by soil properties.

A high-density SNP genotyping array for Brassica napus and its ancestral diploid species based on optimised selection of single-locus markers in the allotetraploid genome - Wayne E. Clarke; Erin E. Higgins; Joerg Plieske; Ralf Wieseke; Christine Sidebottom; Yogendra Khedikar; Jacqueline Batley; Dave Edwards; Jinling Meng; Ruiyuan Li; Cynthia Taylor Lawley; Jérôme Pauquet; et al. (Theoretical and Applied Genetics, 2016)

Persistent CSF but not plasma HIV RNA is associated with increased risk of new-onset moderate-to-severe depressive symptoms; a prospective cohort study - Edward R. Hammond; Rosa M. Crum; Glenn J. Treisman; Shruti H. Mehta; David B. Clifford; Ronald J. Ellis; Benjamin B. Gelman; Igor Grant; Scott L. Letendre; Christina M. Marra; Susan Morgello; David M. Simpson; et al. (Journal of NeuroVirology, 2016)

Subglacial lava propagation, ice melting and heat transfer during emplacement of an intermediate lava flow in the 2010 Eyjafjallajökull eruption - Björn Oddsson; Magnús T. Gudmundsson; Benjamin R. Edwards; Thorvaldur Thordarson; Eyjólfur Magnússon; Gunnar Sigurðsson (Bulletin of Volcanology, 2016)

Breaking out of biogeographical modules: range expansion and taxon cycles in the hyperdiverse ant genus Pheidole - Evan P. Economo; Eli M. Sarnat; Milan Janda; Ronald Clouse; Pavel B. Klimov; Georg Fischer; Benjamin D. Blanchard; Lizette N. Ramirez; Alan N. Andersen; Maia Berman; Benoit Guénard; Andrea Lucky; et al. (Journal of Biogeography, 2015)
Aim We sought to reconstruct the biogeographical structure and dynamics of a hyperdiverse ant genus, Pheidole, and to test several predictions of the taxon cycle hypothesis. Using large datasets on Pheidole geographical distributions and phylogeny, we (1) inferred patterns of biogeographical modularity (clusters of areas with similar faunal composition), (2) tested whether species in open habitats are more likely to be expanding their range beyond module boundaries, and (3) tested whether there is a bias of lineage flow from high‐ to low‐diversity areas. Location The Old World. Methods We compiled and jointly analysed a comprehensive database of Pheidole geographical distributions, the ecological affinities of different species, and a multilocus phylogeny of the Old World radiation. We used network modularity methods to infer biogeographical structure in the genus and comparative methods to evaluate the hypotheses. Results The network analysis identified eight biogeographical modules, and a suite of species with anomalous ranges that are statistically more likely to occur in open habitat, supporting the hypothesis that open habitats promote range expansion. Phylogenetic analysis shows evidence for a cascade pattern of colonization from Asia to New Guinea to the Pacific, but no ‘upstream’ colonization in the reverse direction. Main conclusions The distributions of Pheidole lineages in the Old World are highly modular, with modules generally corresponding to biogeographical regions inferred in other groups of organisms. However, some lineages have expanded their ranges across module boundaries, and these species are more likely to be adapted to open habitats rather than interior forest. In addition, there is a cascade pattern of dispersal from higher to lower diversity areas during these range expansions. Our findings are consistent with the taxon cycle hypothesis, although they do not rule out alternative interpretations.

Range‐wide multilocus phylogeography of the red fox reveals ancient continental divergence, minimal genomic exchange and distinct demographic histories - Mark J. Statham; James Murdoch; Jan Janecka; Keith B. Aubry; Ceiridwen J. Edwards; Carl D. Soulsbury; Oliver Berry; Zhenghuan Wang; David Harrison; Malcolm Pearch; Louise Tomsett; Judith Chupasko; et al. (Molecular Ecology, 2014)
Widely distributed taxa provide an opportunity to compare biogeographic responses to climatic fluctuations on multiple continents and to investigate speciation. We conducted the most geographically and genomically comprehensive study to date of the red fox ( Vulpes vulpes ), the world's most widely distributed wild terrestrial carnivore. Analyses of 697 bp of mitochondrial sequence in ~1000 individuals suggested an ancient Middle Eastern origin for all extant red foxes and a 400 kya ( SD = 139 kya) origin of the primary North American (Nearctic) clade. Demographic analyses indicated a major expansion in Eurasia during the last glaciation (~50 kya), coinciding with a previously described secondary transfer of a single matriline (Holarctic) to North America. In contrast, North American matrilines (including the transferred portion of Holarctic clade) exhibited no signatures of expansion until the end of the Pleistocene (~12 kya). Analyses of 11 autosomal loci from a subset of foxes supported the colonization time frame suggested by mt DNA (and the fossil record) but, in contrast, reflected no detectable secondary transfer, resulting in the most fundamental genomic division of red foxes at the Bering Strait. Endemic continental Y‐chromosome clades further supported this pattern. Thus, intercontinental genomic exchange was overall very limited, consistent with long‐term reproductive isolation since the initial colonization of North America. Based on continental divergence times in other carnivoran species pairs, our findings support a model of peripatric speciation and are consistent with the previous classification of the North American red fox as a distinct species, V. fulva .

The corallivorous flatworm Amakusaplana acroporae: an invasive species threat to coral reefs? - Benjamin C. C. Hume; Cecilia D’Angelo; Anna Cunnington; Edward G. Smith; Jörg Wiedenmann (Coral Reefs, 2014)

Time matters: shifting seasonal migration in Northern Ghana in response to rainfall variability and food insecurity - Christina Rademacher-Schulz; Benjamin Schraven; Edward Salifu Mahama (Climate and Development, 2014)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Forced and unforced variability of twentieth century North American droughts and pluvials - Benjamin I. Cook; Edward R. Cook; Kevin J. Anchukaitis; Richard Seager; Ron L. Miller (Climate Dynamics, 2011)

Volcanology and petrology of Mathews Tuya, northern British Columbia, Canada: glaciovolcanic constraints on interpretations of the 0.730 Ma Cordilleran paleoclimate - Benjamin R. Edwards; James K. Russell; Kirstie Simpson (Bulletin of Volcanology, 2011)

Repurposing climate reconstructions for drought prediction in Southeast Asia - Andrew R. Bell; Benjamin I. Cook; Kevin J. Anchukaitis; Brendan M. Buckley; Edward R. Cook (Climatic Change, 2011)

Root-derived respiration and nitrous oxide production as affected by crop phenology and nitrogen fertilization - Benjamin K. Sey; Ameur M. Manceur; Joann K. Whalen; Edward G. Gregorich; Philippe Rochette (Plant and Soil, 2010)

Impact of socioeconomic status on cancer incidence and stage at diagnosis: selected findings from the surveillance, epidemiology, and end results: National Longitudinal Mortality Study - Limin X. Clegg; Marsha E. Reichman; Barry A. Miller; Benjamin F. Hankey; Gopal K. Singh; Yi Dan Lin; Marc T. Goodman; Charles F. Lynch; Stephen M. Schwartz; Vivien W. Chen; Leslie Bernstein; Scarlett L. Gomez; et al. (Cancer Causes & Control, 2009)

Habitat-specific clutch size and cost of incubation in eiders reconsidered - Markus Öst; Mikael Wickman; Edward Matulionis; Benjamin Steele (Oecologia, 2008)

No variation of physical performance and perceived exertion after adrenal gland stimulation by synthetic ACTH (Synacthen®) in cyclists - Norbert Baume; Graeme Steel; Tony Edwards; Eric Thorstensen; Benjamin F. Miller (European Journal of Applied Physiology, 2008)

A cross‐taxa phenological dataset from Mohonk Lake, NY and its relationship to climate - Benjamin I. Cook; Edward R. Cook; Paul C. Huth; John E. Thompson; Anna Forster; Daniel Smiley (International Journal of Climatology, 2008)
We present a detailed analysis of a rare cross‐taxa native species phenology dataset (plant flowering, insect first sighting, and amphibian first sighting) from Mohonk Lake, NY. This dataset is highly unusual in North America for its longevity of record, consistency of methodology and location, diversity of species available, and availability of local daily meteorological data. For each phenology series, we examined the flowering and first sighting Julian calendar dates for the existence of temporal trends. Only one of the five animal species (katydid) showed any evidence for a significant trend in first sighting. In contrast, the plant species showed a rich mixture of temporal trends in flowering that could be divided into four classes: woody plant–no trend, woody plant–negative trend, herbaceous plant–negative trend, and herbaceous plant–positive trend. Many of the trends were found to be statistically significant and robust to the method of trend estimation. The data within each of the four plant classes were also pooled as anomalies to provide more complete temporal coverage for tests of trend robustness. The results were strongly consistent with the trends of the individual species within each class and highly significant statistically. We next correlated the flowering and first sighting dates against growing degree‐day (GDD) summations for each day of the year to measure the sensitivity of each species to this common form of climatic forcing on phenology. All species showed a significant sensitivity to GDD summations, with peak correlations falling on or near the varying median flowering or first sighting dates. These results were robust whether the GDD analyses were conducted over the complete set of observations for each species (beginning on or after 1928) or over a latter period with a more serially complete set of cross‐taxa observations (1970–2002). The GDD correlations indicate significant climate sensitivity in all species, but the different magnitudes of correlation and timing of maximum correlation imply that plant and animal responses to climate changes in the future will not be homogeneous for the tested species at Mohonk Lake. Copyright © 2007 Royal Meteorological Society

Quality of race, Hispanic ethnicity, and immigrant status in population-based cancer registry data: implications for health disparity studies - Limin X. Clegg; Marsha E. Reichman; Benjamin F. Hankey; Barry A. Miller; Yi D. Lin; Norman J. Johnson; Stephen M. Schwartz; Leslie Bernstein; Vivien W. Chen; Marc T. Goodman; Scarlett L. Gomez; John J. Graff; et al. (Cancer Causes & Control, 2007)

Structure–activity relationships of dinucleotides: Potent and selective agonists of P2Y receptors - Sammy R. Shaver; Janet L. Rideout; William Pendergast; James G. Douglass; Edward G. Brown; José L. Boyer; Roshni I. Patel; Catherine C. Redick; Arthur C. Jones; Maryse Picher; Benjamin R. Yerxa (Purinergic Signalling, 2005)

Comparative effects of tobacco smoking and nasal nicotine - Christian Teter; Benjamin Asfaw; Lisong Ni; Mark Lutz; Edward Domino; Sally Guthrie (European Journal of Clinical Pharmacology, 2002)

Partitioning linear trends in age-adjusted rates - Benjamin F. Hankey; Lynn A. Ries; Carol L. Kosary; Eric J. Feuer; Ray M. Merrill; Limin X. Clegg; Brenda K. Edwards (Cancer Causes & Control, 2000)

Is observed variability in the long‐term results of the Continuous Plankton Recorder survey a response to climate change? - PHILIP C. REID; BENJAMIN PLANQUE; MARTIN EDWARDS (Fisheries Oceanography, 1998)
In the more than 50 years that the Continuous Plankton Recorder (CPR) survey has operated on a regular monthly basis in the north‐east Atlantic and North Sea, large changes have been witnessed in the planktonic ecosystem. These changes have taken the form of long‐term trends in abundance for certain species or stepwise changes for others, and in many cases are correlated with a mode of climatic variability in the North Atlantic, either: (1) the North Atlantic Oscillation (NAO), a basin‐scale atmospheric alteration of the pressure field between the Azores high pressure cell and the Icelandic Low; or (2) the Gulf Stream Index (GSI), which measures the latitudinal position of the north wall of the Gulf Stream. Recent work has shown that the changes in the GSI are coupled with the NAO and Pacific Southern Oscillation with a 2 year lag. The plankton variability is also possibly linked to changes observed in the distribution and flux of water masses in the surface, intermediate and deep waters of the North Atlantic. For example, in the last two decades, the extent and location of the formation of North Atlantic Deep Water, Labrador Sea Intermediate Water and Norwegian Sea intermediate and upper‐layer water has altered considerably. This paper discusses the extent to which observed changes in plankton abundance and distribution may be linked to this basin‐scale variability in hydrodynamics. The results are also placed within the context of global climate warming and the possible effects of the observed melting of Arctic permafrost and sea ice on the subpolar North Atlantic.